2021
DOI: 10.1053/j.gastro.2020.12.068
|View full text |Cite
|
Sign up to set email alerts
|

An Update on the Epidemiology, Molecular Characterization, Diagnosis, and Screening Strategies for Early-Onset Colorectal Cancer

Abstract: Rising trends in the incidence and mortality of early-onset CRC in those who are ages less than 50 years have been well-established. These trends have spurred intense investigation focused on elucidating the epidemiology and characteristics of early-onset CRC, as well on identifying strategies for early detection and prevention. In this review, we provide a contemporary update on early-onset CRC with a particular focus on epidemiology, molecular characterization, red flag signs and symptoms, and screening for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
140
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 179 publications
(158 citation statements)
references
References 79 publications
1
140
1
1
Order By: Relevance
“…Colorectal cancer (CRC) is the third most common malignancy worldwide ( Burnett-Hartman et al, 2021 ). Development of CRC is a multifactorial process with known risk factors including older age, male sex, family history, and unhealthy lifestyle including a dysregulated diet with low intake of fresh fruits and vegetables, obesity, smoking, and lack of exercise ( Frank et al, 2021 ; Sehgal et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal cancer (CRC) is the third most common malignancy worldwide ( Burnett-Hartman et al, 2021 ). Development of CRC is a multifactorial process with known risk factors including older age, male sex, family history, and unhealthy lifestyle including a dysregulated diet with low intake of fresh fruits and vegetables, obesity, smoking, and lack of exercise ( Frank et al, 2021 ; Sehgal et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…A variety of tumors, including pancreatic cancer, possess different molecular characteristics, biological behaviors and therapeutic responses in different age groups ( 17 19 ). For example, young patients and elderly patients with pancreatic cancer benefit from comprehensive treatment differently.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this study was the first research to specifically investigate the survival effect of radiotherapy on different ages of patients with stage II/III RC. Numerous tumors exhibit differences in molecular background, biological behavior, etiology as well as therapeutic response among various age groups (9,(14)(15)(16)(17)(18). A recent research study focusing on young breast cancer patients found that chemotherapy was an S1).…”
Section: Discussionmentioning
confidence: 99%